Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1530/eje-13-0624
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Genetics of FSH action: a 2014-and-beyond view

Abstract: Objective: To assess the pharmacogenetic potential of FSH for infertility treatment. Design: Review of the literature and genomic databases. Methods: Single-nucleotide polymorphism (SNP) assessed: rs6166 (c.2039AOG, p.N680S), rs6165 (c.919AOG, p.T307A), rs1394205 (c.K29GOA) in FSHR, and rs10835638 (c.K211GOT) in FSHB. Literature search via PubMed. Blast analysis of genomic information available in the NCBI nucleotide database. Comparison of allele frequency and haplotype distribution using the http://spsmart.c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 86 publications
(124 reference statements)
6
89
2
Order By: Relevance
“…This frequency distribution compares well to what have been reported from other countries (9, 13, 31). …”
Section: Resultssupporting
confidence: 89%
“…This frequency distribution compares well to what have been reported from other countries (9, 13, 31). …”
Section: Resultssupporting
confidence: 89%
“…Allelic variants of FSHR determine different FSHR sensitivity's [20,24,26]. Because of that we expected to find that FSHR 's variants influence in the reproduction outcomes, in our results we observed that the number of MII oocytes and embryos are higher in Ala307Ala women.…”
Section: Discussionmentioning
confidence: 50%
“…Perez Mayorga et al [20] was the first group that observed differences in Asn680Ser genotypes with dose of rFSH in COH. Other groups observed that the FSHR variants influence the basal FSH and estradiol levels with conflicting results [23,24,25,26,27], for this reason, the FSHR gene and others gene variations may play a role in modulating receptor sensitivity and intracellular second messenger cascades to exogenous hCG and other gonadotrophins [24,28], thus the FSHR SNPs may cause changes in the phosphorylation and glycosylation molecular mechanisms [29,30]. …”
Section: Introductionmentioning
confidence: 99%
“…Genetic variants in Caucasian and African American women have also been predictive of AMH and FSH levels, with important implications on FSH serum levels, receptor sensitivity to FSH, and response to stimulation (64,67,68). Finally, three studies in this review also found significantly higher peak E2 levels, which may affect implantation, in black women compared with white women, and two reported this finding in Asian women (20, 22, 26, 36, 48).…”
Section: Ovarian Function and Hormone Levelsmentioning
confidence: 73%